(untitled) (Global Journal of Science Frontier Research, 2016)
In the present paper, we define a new type of connection called semi-symmetric Sconnection in a generalised co-symplectic manifold and studied some of its properties. The relation between the curvature tensor with respect to this connection and the curvature tensor with respect to the Riemannian connection is establised.